Patterns of epithelial cell abnormalities in Pap smears and its clinicopathological and demographic association: a descriptive study from Visakhapatnam city, Andhra Pradesh, India - Lakshmi, A. Bhagya; Madhavi, B. Devi; Vasundhara, M.; Sri, K. Satya; Vani, I.; Sreelekha, A. (International Journal of Research in Medical Sciences, 2017)
Background: Cervical cancer is one of the leading cancers amongst women. Periodic pap screening is the simplest way to diagnose precancerous lesions. Factors such as ignorance, poverty poorly developed public healthcare delivery system put women in urban slums at a disadvantage for receiving any health screening activity. Objectives of the present study were to know the prevalence of epithelial cell abnormalities of the cervix among the subjects and to study the association with clinical and demographic characteristics. Methods: A camp based descriptive study was conducted in an urban ward. All women above the age of 20 years were included in the study. Data was recorded using a pretested questionnaire. Study variables included socio-demographic characteristics, symptoms of reproductive tract infection, findings of clinical examination, and Pap smear collection and evaluation. The latter was done from 194 women aged between 20-69 years. Pap smears were made by conventional Pap smear technique and reported according to The Revised Bethesda System of classification 2001(TBS). Results: Among the 194 women, in 8 subjects, the smears collected were unsatisfactory for evaluation. Analysis was done in the remaining 186 subjects. Among the latter, in 83.9%, the smears were negative for intraepithelial lesions (NIEL) and 16.1% revealed epithelial cell abnormalities (ECA). Among those with ECA, Atypical cells of undetermined significance (ASCUS) was identified in 66.67%, Low grade squamous intraepithelial lesions(LSIL) in 16.67%, Atypical squamous cells-cannot exclude HSIL (ASC-H) and Atypical glandular cells-not otherwise specified (AGC-NOS) in 6.67% each and High grade squamous intraepithelial lesions (HSIL) in 3.33%. Epithelial cell abnormalities were more common in women in the age group of 30-60 years (80%), they were more common in those with age at marriage between 13-18 years (63.3%) and in those with age at first child birth between 15-19 years (56.7%). Conclusions: Therefore there is a need for Pap screening at regular intervals through camp based approach in these populations to motivate the women, increase their awareness, ensure follow up and referral and timely intervention in appropriate cases.